2021
DOI: 10.48550/arxiv.2109.09482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ground states for the planar NLSE with a point defect as minimizers of the constrained energy

Abstract: We investigate the ground states for the focusing, subcritical nonlinear Schrödinger equation with a point defect in dimension two, defined as the minimizers of the energy functional at fixed mass. We prove that ground states exist for every positive mass and show a logarithmic singularity at the defect. Moreover, up to a multiplication by a constant phase, they are positive, radially symmetric, and decreasing along the radial direction. In order to overcome the obstacles arising from the uncommon structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…After first investigations on star graphs (see e.g. [4]), the behaviour of (4) on general non-compact graphs with half-lines has been characterized in [13,15] for L 2 -subcritical nonlinearities p ∈ (2,6) and in [16] for the L 2 -critical regime p = 6. In particular, it has been shown that whether ground states at a certain mass exist strongly depends both on topological and on metric properties of the graph.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After first investigations on star graphs (see e.g. [4]), the behaviour of (4) on general non-compact graphs with half-lines has been characterized in [13,15] for L 2 -subcritical nonlinearities p ∈ (2,6) and in [16] for the L 2 -critical regime p = 6. In particular, it has been shown that whether ground states at a certain mass exist strongly depends both on topological and on metric properties of the graph.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…On the other hand, fueled for instance by possible applications as the dynamic of confined charges [43,49] or the resonant tunneling [52], concentrated nonlinearities have been proposed. In Euclidean spaces, models describing the effect of a delta potential have been considered first in dimension one and three [9,10,17,18] (see also the recent papers [40,41]), whereas the analysis in dimension two is more recent [2,7,8,28,29,37]. On non-compact graphs, the presence of a single standard nonlinearity restricted to the compact core of the graph (i.e.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When Vpxq " 0, it arises in various physical contexts such as nonlinear optics and plasma physics [30]. When V is chosen as Dirac's delta function, it can be used to model a Bose-Einstein Condensation (BEC) in the presence of point defects or impurities [1,24]. Besides, recently, it has attracted a lot of attention when V is an inverse power potential (see [17,20,23] and references therein).…”
Section: Introductionmentioning
confidence: 99%